Disparities in Vision Impairment and Eye Diseases among Early Late-Life Women: The Study of Women's Health Across the Nation, Michigan Site. (17th November 2022) - Karvonen-Gutierrez, Carrie A; Hood, Michelle M.; Moroi, Sayoko; Musch, David C.; Kumar, Navasuja; Wood, Sarah Dougherty
ABSTRACT: Objective: To quantify the burden of vision impairment (VI) and ocular conditions among early late-life women. Methods: Women ( n = 254, mean age 66.0 years) participated in a comprehensive vision assessment. Visual acuity (VA) and ocular disorders (diabetic retinopathy, macular degeneration, hypertensive retinopathy, glaucoma and cataracts) were defined clinically. Race, economic strain and education were self-reported. Results: The prevalence of presenting VI (VA 20/40 or worse) was 11.0% and 75% of that was correctable (best-corrected VI 2.8%). Black women and those with greater economic strain or less education had a higher prevalence of presenting VI. These disparities were no longer present after considering best-corrected VI. Ocular disease prevalence ranged from 3.3% (age-related macular degeneration) to 30.2% (hypertensive retinopathy), but most participants were unaware of their ocular diagnosis. Conclusion: The discordance of presenting versus best-corrected VI and lack of knowledge of ocular conditions suggests a need for increased vision services. Access to optimal vision correction may attenuate differences across sociodemographic groups.